2016
DOI: 10.1093/jpepsy/jsw046
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Maternal and Paternal Pain-Related Attitudes, Behaviors, and Perceptions across Pediatric Pain Rehabilitation Treatment: A Multilevel Modeling Approach

Abstract: Results indicate the efficacy of this treatment model for both children with chronic pain and their parents and highlights the importance of parental presence in treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…As a result, it can be challenging to identify parents’ role in treatment while balancing functional independence and accountability. Two recent studies have demonstrated that parent behavior changes positively relates to children’s pain and function outcomes when parents are included in children’s interdisciplinary inpatient pain treatment [77,78]. In this section, we describe the creation of a parent education program delivered in the context of an inpatient pain rehabilitation program, the Functional Independence Restoration (FIRST) program, and examine parents’ responses to the implementation.…”
Section: Methods Measures and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, it can be challenging to identify parents’ role in treatment while balancing functional independence and accountability. Two recent studies have demonstrated that parent behavior changes positively relates to children’s pain and function outcomes when parents are included in children’s interdisciplinary inpatient pain treatment [77,78]. In this section, we describe the creation of a parent education program delivered in the context of an inpatient pain rehabilitation program, the Functional Independence Restoration (FIRST) program, and examine parents’ responses to the implementation.…”
Section: Methods Measures and Resultsmentioning
confidence: 99%
“…Parents participated in weekly one-hour parent education group sessions as part of their child’s treatment in our intensive inpatient pediatric pain rehabilitation program. There are few published assessments of parent specific education programs within pediatric pain rehabilitation programs [78]. On average, group size was 2.5 parents per session.…”
Section: Methods Measures and Resultsmentioning
confidence: 99%
“…Physiological and rehabilitative interventions for pediatric chronic pain, including physical and occupational therapy, focus on improving physical functioning by progressively engaging children in previously avoided activities and taking a self-management approach to pain [16,17]. The goal of these interventions is to improve strength, flexibility, endurance, joint stability, tolerance for weight-bearing, coordination, balance, and proprioception [5,18,19,20].…”
Section: State Of the Art Of Rehabilitation For Pediatric Chronic mentioning
confidence: 99%
“…The joint variables are defined as the sets of angles or extensions between the successive body segments, depending on the degrees of freedom of the joint in a rotational or sliding joint, respectively. Importantly, it is a meaningful technique to determine the recovery condition of a patient from the rehabilitation treatment . Particularly, obtaining real‐time tracking data of the patient's residual motor functionalities will be a significant achievement in the field of rehabilitation study, since it is extremely difficult based on current commercial monitoring systems.…”
Section: Introductionmentioning
confidence: 99%